Rural School-Based Mental Health Services: Parent Perceptions of Needs and Barriers. Issue 2 (16th February 2018) - van Vulpen, Kimberly Searcey; Habegar, Amy; Simmons, Teresa
Abstract: The benefits of school-based mental health services have been supported in prior research and literature. Studies have shown that approximately one in five youths in schools today have diagnosable mental health disorders. However, research has identified that close to 70 percent of those youths do not receive the services they need. This gap in care has a significant impact on the academic, social, and emotional well-being of youths. Parent involvement is essential in bridging services. However, parents often face barriers in accessing mental health care for their child. The aim of this study was to explore parent perceptions of needs and barriers to school-based mental health services. This exploratory study included 607 parent and guardian respondents. Findings showed that parents were overwhelmingly in support of schools being involved in addressing the mental health needs of students. Anxiety, depression, and bullying were the top emotional and behavioral issues that parents recognized as the main challenge for their child. Lack of parent support, understanding that mental health issues even exist in youths, and lack of supportive school programs were identified as key factors that place youths at risk of not receiving the services they need.